Assessment of biodiversity data holdings and user data needs for Ghana - Asase, Alex; Schwinger, Gladys O (Biodiversity Informatics, 2018)
Data on biodiversity are important to addressing the challenges of sustainable development, and for decision-making about natural resources and environments. Biodiversity information, when mobilized and shared openly, has the potential to impact science and conservation positively. However, biodiversity data mobilization is expensive, such that data mobilization and sharing activities must be prioritized to meet the needs of the user community. In this study, we undertook a detailed assessment of biodiversity data holdings and user needs in Ghana through semi-structured questionnaire interviews, and focus-group discussions in the form of a workshop. Most biodiversity data-holding organizations were at preliminary stages of digital biodiversity data mobilization and sharing. Taxonomic, checklist, and geographic data on plants and animals were identified as most needed. Priority thematic needs were as regards protected areas, invasive alien species, threatened species, economic species (timber and non-timber forest products), and pathogens and diseases. Human and infrastructural capacities, and sustainable coordination were identified as the major challenges to biodiversity data management. This study provides a detailed case study of how assessing biodiversity data holdings and user data needs can be used to strategize biodiversity data mobilization, data publication, and data use activities.